Generalized extensive cutaneous nodules as a first presentation of plasmablastic lymphoma in an immunocompetent patient: A case report and literature review - Eman Al Mussaed (Wolters Kluwer Medknow Publications, 2017)
Plasmablastic lymphoma (PBL) is a rare aggressive non-Hodgkin lymphoma, frequently involving the jaw and oral mucosa in human immunodeficiency virus (HIV)-positive patients and is also often associated with Epstein-Barr virus infection, occurring mostly in men. However, a number of cases have been reported in extraoral sites and in immunocompetent patients. There have been no reported cases of PBL without immunodeficiency disease from Saudi Arabia presented by extensive cutaneous involvement. Here, we report a rare case of PBL in a 20-year-old man without immunodeficiency diseases, HIV negative, and presenting with generalized extensive cutaneous nodules as a first presentation due to infiltration by neoplastic cells.